Hukum Pemanfaatan Dana Zakat untuk Melaksanakan Pernikahan Massal (Studi Kasus Wahdah Inspirasi Zakat Wahdah Islamiyah Makassar) - Ronny Mahmuddin; Asri Asri; Audrion Maulana (AL-KHIYAR: Jurnal Bidang Muamalah dan Ekonomi Islam, 2022)
This study aims to: 1) find out how the mechanism for utilizing zakat funds for jama'i/e.g. weddings: 2) find out to what extent the use of zakat funds for mass weddings/jama'i is on target: and 3) explain Islamic law regarding the use of funds. zakat for jama`i/mass marriages. This research is a field research (field research). The subject of this research is WIZ Wahdah Islamiyah. Data collection methods in this study are interviews, direct observation or observation, and documentation. The results of the study can be concluded that: 1) The mechanism for implementing the use of zakat funds to carry out jama`iyah weddings/mass weddings at WIZ Wahdah is the distribution of circulars by the Wahdah Islamiyah Central Executive Board to the Wahdah Islamiyah Regional Leadership Councils in various regions and higher education institutions that under the auspices of the Wahdah Education Foundation, the opening of registration of prospective participants for jama'i/mass marriage activities and selection of file requirements and general requirements for activities, WIZ Wahdah Islamiyah conducts direct surveys, submits proposals for activity funds to WIZ Wahdah Islamiyah, conducts pre-wedding cycles, and qabul consent and walimah jama'i reception. 2) Utilization of zakat funds for jama`i/mass weddings at WIZ Wahdah has been carried out three times, namely in 2015, 2018, and 2019 using free infaq funds, using these funds to carry out walimah jama'i receptions. 3) The legal stipulation of the use of zakat funds to carry out jama'i/mass marriages is taken from the ijtihad of the ulama and the agreement of the WIZ Wahdah Islamiyah sharia board, namely it is permissible to use zakat funds for jama'i/mass marriages.